Maternal nicotine exposure aggravates metabolic associated fatty liver disease via PI3K/Akt signaling in adult offspring mice. (11th May 2021) - Huang, Shu‐Jing; Chen, Shu‐qiang; Lin, Yan; Yang, Hong‐Yi; Ran, Jing; Yan, Fang‐Fang; Huang, Mei; Liu, Xian‐Lan; Hong, Long‐Cheng; Zhang, Xiao‐Dong; Lyu, Guo‐Rong; Wang, Zhan‐Xiang; et al.
Abstract: Aim: The aim of this study is to investigate the effect of maternal nicotine exposure (MNE) on the development of metabolic associated fatty liver disease (MAFLD) in adulthood offspring and the underlying mechanism. Methods: Pregnant mice (n = 22) were subcutaneously injected with either saline vehicle (n = 11) or nicotine (n = 11) twice a day on gestational days 11‐21. Offspring mice (n = 176) from both groups were weaned at postnatal day 21, and for 6 months after postnatal day 21, 96 mice were fed either a standard chow diet (n = 48) or a high‐fat diet (n = 48). Serum lipid indicators, liver function indicators, insulin, and liver mitochondrial respiration were analyzed. The expression levels of fibrosis‐related proteins, phosphorylated PI3K, phosphorylated Akt, sterol regulatory element‐binding transcription factor 1 (SREBP1c), and peroxisome proliferator‐activated receptor alpha (PPAR‐α) were detected in the liver by immunohistochemistry and Western blotting. Results: MNE significantly decreased the weight of both maternal and offspring mice (~30%) and inhibited organ growth in offspring mice ( P  < .05). MNE also significantly increased serum levels of total bile acid, triglycerides, total cholesterol, glucose, alanine aminotransferase, aspartate aminotransferase, low‐density lipoprotein, and insulin while decreasing serum high‐density lipoprotein levels and mitochondrial respiration activity in mice fed either the normal diet or high‐fat diet (all P  < .05). These effects of MNE on lipid metabolism and insulin resistance were mediated via PI3K and Akt phosphorylation and down‐regulation of SREBP1c and PPAR‐α. Conclusion: Our data indicate MNE induces lipid metabolism disorder and insulin resistance to promote MAFLD progression in adult offspring through activation of PI3K/Akt signaling and suppression of SREBP1c and PPARα protein expression.